Features of formation of productivity of sugar beets hybrids of domestic breeding - М. В. Роїк; О. І. Присяжнюк; Н. О. Кононюк; О. Г. Кулик (Plant Varieties Studying and Protection)
Purpose. To reveal features of formation of productivity of modern sugar beet hybrids of domestic selection.